The Impact of ROA and DAR on The BEI F&B Stock Price During Covid-19 - Asriani Hasan; Andi Risfan Rizaldi (Integrated Journal of Business and Economics (IJBE), 2023)
This study is about the Impact of ROA and DAR on Stock Prices in companies of Food and beverage companies listed on the Bursa Efek Indonesia (BEI). This study uses the annual financial report data and average data closing price of shares in 2021. In this study, the amount of data used as a sample is 30 companies. The data sources used are www.idx.co.id and www.financeyahoo.com. This study uses multiple linear regression analysis methods to see the influence of ROA and DAR on stock prices. The results obtained based on the chosen analytical method are that there is a positive and significant influence on the variable return on assets (ROA) on stock prices. Furthermore, the variable of DAR on stock price has a negative and insignificant impact.